Clear cell renal cell carcinoma micrometastasis: Insights from an unconventional cutaneous presentation - Mohammad Fardos; Heather Kopecky; James Sligh; Jill Browning (Wiley, 2024)
Abstract Clear cell renal cell carcinoma (ccRCC) is a highly lethal cancer known for its propensity to metastasise, yet the mechanisms underlying metastasis are not well defined. Cutaneous metastases from ccRCC are uncommon and typically occur within 3 years post‐nephrectomy, predominantly affecting the scalp, chest or abdomen. Here, we present a unique case of a 75‐year‐old male, previously treated for ccRCC with right radical nephrectomy, who developed a singular skin lesion on the left side of the neck 19 years post‐nephrectomy. The lesion was confirmed as metastatic ccRCC through histopathological analysis, despite negative imaging findings. Micrometastases, characterised by microscopic tumour cell foci in distant sites, pose a significant diagnostic challenge, frequently evading detection on conventional imaging modalities like computed tomography and magnetic resonance imaging. This case contributes to our understanding of ccRCC metastasis, emphasising the necessity for continued clinical vigilance and thorough diagnostic scrutiny, particularly concerning atypical metastatic sites.